Human postural response to lower leg muscle vibration of different duration - Capicíková, N; Rocchi, L; Hlavacka, F; Chiari, L; Cappello, A (Physiological research, 2006)
Body lean response to bilateral vibrations of soleus muscles were investigated in order to understand the influence of proprioceptive input from lower leg in human stance control. Proprioceptive stimulation was applied to 17 healthy subjects by two vibrators placed on the soleus muscles. Frequency and amplitude of vibration were 60 Hz and 1 mm, respectively. Vibration was applied after a 30 s of baseline. The vibration duration of 10, 20, 30 s respectively was used with following 30 s rest. Subjects stood on the force platform with eyes closed. Postural responses were characterized by center of pressure (CoP) displacements in the anterior-posterior (AP) direction. The CoP-AP shifts as well as their amplitudes and velocities were analyzed before, during and after vibration. Vibration of soleus muscles gradually increased backward body tilts. There was a clear dependence of the magnitude of final CoP shift on the duration of vibration. The amplitude and velocity of body sway increased during vibration and amplitude was significantly modulated by duration of vibration as well. Comparison of amplitude and velocity of body sway before and after vibration showed significant post-effects. Presented findings showed that somatosensory stimulation has a long-term, direction-specific influence on the control of postural orientation during stance. Further, the proprioceptive input altered by soleus muscles vibration showed significant changes in postural equilibrium during period of vibration with interesting post-effects also.
Keywords: dospělí; kosterní svaly; bérec; Female; Adult; Leg; vibrace; ženské pohlaví; propriocepce; lidé; postura těla; Postural Balance; Muscle, Skeletal; Vibration; Male; Posture; lidé středního věku; mužské pohlaví; Proprioception; Middle Aged; posturální rovnováha; Humans